THE LINK BETWEEN ECO-INNOVATION AND PERFORMANCE OF CREATIVE INDUSTRY OF MARBLE AND NATURAL STONE CRAFT - Astuti, Murti; Pratikto, Pratikto; Irawan, Yudy Surya; Sugiono, Sugiono (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
This study investigates the effect of eco-innovation on creative industry production performance of marble and natural stone craft sector in Tulungagung, Indonesia. Mostly, the companies are in form of small and medium-sized enterprises (SMEs) which is ‘passive eco-innovator’ and their eco-innovation variables have not been investigated before in terms of their influence on their performance. The respondents were 81 craftsmen taken from the population. The data were collected through questionnaires which were tested, processed and analyzed by using consistent Partial Least Squares – Structural Equation Modeling (PLSc-SEM). From this study, it can be concluded that in creative industries center of marble and natural stone crafts in Tulungagung, eco-marketing innovation significantly influence on eco-process innovation, but not significantly influence on eco-product innovation. Implementation of eco-process innovation significantly influence on eco-product innovation. Eco-product innovation significantly influence on production performance but not significantly influence on market performance. Production performance significantly influence financial performance.